Survival by AIDS defining condition in rural Uganda. Issue 3 (1st June 2000) - Morgan, D; Malamba, S S; Orem, J; Mayanja, B; Okongo, M; Whitworth, J A G
Abstract : Objectives: To report the initial AIDS defining conditions, CD4 lymphocyte counts around the time of AIDS diagnosis, and survival by AIDS defining condition in a population based cohort in rural Uganda. Methods: Participants in an HIV natural history cohort in rural Uganda were reviewed every 3 months at routine visits and at other times when they were ill. The date and nature of the first AIDS defining condition in participants developing AIDS during follow up between the start of the cohort in 1990 and the end of 1998 were noted. The CD4 count at, or within, 3 months of this time was recorded for those participants who developed AIDS (WHO stage 4) after 1993. Results: The median survival from developing AIDS to death was 9.3 months and the median CD4 lymphocyte count around the time of developing AIDS was 150 cells ×10 6 /l. The most frequent AIDS defining conditions were wasting syndrome, oesophageal candidiasis, and mucocutaneous herpes simplex virus infection (HSV) for more than 1 month. The median survival with wasting syndrome, Kaposi's sarcoma, and oesophageal candidiasis was less than 3.5 months; however, survival with cryptosporidial diarrhoea, chronic HSV, and extrapulmonary tuberculosis was greater than 20 months. There was little relation between CD4 count around the time of development of the AIDS defining condition and the median survival with that condition. Conclusions: The survival for most AIDS defining conditions was generally shorter and the median CD4 lymphocyte count higher than studies reported from developed countries. However, the conditions with the longest survival (cryptosporidial diarrhoea, chronic HSV, and extrapulmonary tuberculosis) had a similar survival to that in developed countries and these conditions have a high background level in this population.